Implementation of an Internet Weight Loss Program in a Worksite Setting - Kathryn M. Ross; Rena R. Wing (Journal of Obesity)
Background. Worksite wellness programs typically produce modest weight losses. We examined whether an efficacious Internet behavioral weight loss program could be successfully implemented in a worksite setting. Methods. Participants were 75 overweight or obese employees/dependents of a large healthcare system who were given access to a 12-week Internet-based, multicomponent behavioral weight loss program. Assessments occurred at baseline, Month 3 (end of intervention), and Month 6 (follow-up). Results. Retention was excellent (93% at Month 3 and 89% at Month 6). Intent-to-treat analyses demonstrated that participants lost an average (±SE) of -5.8±.60 kg from baseline to Month 3 and regained 1.1±.31 kg from Month 3 to Month 6; overall, weight loss from baseline to Month 6 was -4.7±.71 kg, p<.001. Men lost more weight than women, p=.022, and individuals who had a college degree or higher lost more weight than those with less education, p=.005. Adherence to viewing lessons (8 of 12) and self-monitoring (83% of days) was excellent and significantly associated with weight loss, ps<.05. Conclusions. An Internet-based behavioral weight management intervention can be successfully implemented in a worksite setting and can lead to clinically significant weight losses. Given the low costs of offering this program, it could easily be widely disseminated.